Family members´ experiences of the end-of-life care environments in acute care settings – a photo-elicitation study. Issue 1 (1st January 2018) - Hajradinovic, Yvonne; Tishelman, Carol; Lindqvist, Olav; Goliath, Ida
ABSTRACT: Purpose: This article explores experiences of the acute-care environment as a setting for end-of-life (EoL) care from the perspective of family members of a dying person. Method: We used participant-produced photographs in conjunction with follow-up interviews with nine family members to persons at the EoL, cared for in two acute-care settings. Results: The interpretive description analysis process resulted in three constructed themes—Aesthetic and un-aesthetic impressions, Space for privacy and social relationships, and Need for guidance in crucial times. Aspects of importance in the physical setting related to aesthetics, particularly in regard to sensory experience, and to a need for enough privacy to facilitate the maintenance of social relationships. Interactions between the world of family members and that of professionals were described as intrinsically related to guidance about both the material and immaterial environment at crucial times. Conclusion: The care environment, already recognized to have an impact in relation to patients, is concluded to also affect the participating family members in this study in a variety of ways.